Civic Identity in the Context of the Modern Global Psychological Thought - Petrovska, Inga (Psychological Prospects Journal, 2016)
Analysis of modern theoretical concepts of civic identity revealedeclectic understanding of the concept of civic identity, insufficient justification of its understanding as a separate category without the reference to the categories of citizenship or national identity and consciousness, which inevitably leads to reductionism in its study (either of educational or politological, social-historical nature). Non-systemic understanding of the relationships between various social andpolitical identities of an individual, mutually contradictory views as to both the content of dominant and subordinate levels of the hierarchy of respective identities and their structure result in the diversity, fragmentation of the scientific ideas about identity in general and civic identity in particular. We should note the reduction of scientific dispositions as to the study of civil identity outside the context ofglobalization–anti-globalization trends in the societies development, both Western and Eurasian. The deployment of global politics processes causes the strengthening of emigration−immigration movements and readiness of a modern human to deliberately change nationality (with stable ethnic and religious identity). Globalization involvesabstraction of civil identity from ethnic and other socio-biological characteristics and its dominance over other types of identities. In modern science, there is a rather acute problem of how civic identity can combine all the features of abstraction (nonattachment to the characteristics of the territory, ethnicity, religion) and specificity (i. e. remaining functional, effective, influential in the context of the other personality formations). Civic identity should be studied in the context of rapid, unpredictable and sometimes controversial dynamics, tendency to abstraction, the formation of supranational identities. There is a need to develop adequate consistent understanding of civil identity as a distinct social and psychological category, holistic concept of civic identity which would include a model of its structure and types.Keywords: civil identity, ethnic identity, national identity, European identity, citizenship, nationality.